Physical basis of apparent pore-dilation of ATP-activated P2X receptor channels - Li, Mufeng (Nat Neurosci, 2015)
The selectivity of ion channels is fundamental for their roles in electrical and chemical signaling, and ion homeostasis. Although most ion channels exhibit stable ion selectivity, the prevailing view for purinergic P2X receptor channels, transient receptor potential V1 (TRPV1) channels and acid sensing ion channels (ASICs) is that their ion conduction pores dilate upon prolonged activation. We investigated this mechanism in P2X receptors and found that the hallmark shift in equilibrium potential observed with prolonged channel activation does not result from pore dilation, but from time-dependent alterations in the concentration of intracellular ions. We derived a physical model to calculate ion concentration changes during patch-clamp recordings, which validates our experimental findings and provides a quantitative guideline for effectively controlling ion concentration. Our results have fundamental implications for understanding ion permeation and gating in P2X receptor channels, and more broadly for using patch-clamp techniques to study ion channels and neuronal excitability.